Drivers of soil carbon dioxide efflux in a 70 years mixed trees species of Tropical Lowland Forest, Peninsular Malaysia - Mande, K.H.; Abdullah, A.M.; Zaharin, A.A.; Ainuddin, A.N. (Universiti Kebangsaan Malaysia, 2014)
Forest biomass is a major component in carbon sequestration and a driver of heterotrophy and autotrophy soil CO2 efflux, as it accumulation increases carbon organic nutrients, root growth and microbial activity. Understanding forest biomass rational to ascertain the forest ecosystems productivity is important. A study has been conducted in a 70-year-old forest of mixed tree species, Sungai Menyala Forest, Port Dickson, Peninsular Malaysia, measuring the total above ground biomass (TAGB), below ground biomass (BGB), total forest carbon (SOCs), soil organic carbon stock (SOCstoc) and soil CO2 efflux from 1 February to 30 June 2013. The aim was to determine the effect of forest biomass, litter fall and influence of environmental factors on soil CO2 efflux. Multiple regression analysis has been conducted on the relationship between the variables and the soil CO2 efflux. Soil CO2 efflux was found to range from 92.09-619.67 mg m-2 h-1, with the amount of the tropical forest biomass estimated at 1.9×106, 7.7×106 and 9.2×105 kg for TAGB, BGB and SOCs, respectively. The analysis showed a strong correlation between soil CO2 efflux and soil temperature, soil moisture, water potential and forest carbon input with R2 more than 0.89 at p<0.01. The findings showed a strong contribution from forest biomass as drivers of heterotrophy and autotrophy soil CO2 efflux. We can conclude that the forest biomass and environmental factors are responsible for the remarkable variation in soil CO2 efflux, as climate change can cause increase in temperature as well as deforestation decreases forest biomass.